2019
DOI: 10.3846/mbmst.2019.113
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Portland cement composites containing high amounts of different kinds of fly ashes

Abstract: Utilization of fluidized fly ash in cement composite is problematic, e.g. because of its changeable chemical composition and increased water demand of the mixture. However, this kind of by-product shows some self-cementing properties, which may be beneficial for low-cement mixtures. The article compares the impact of various kinds of fly ashes, i.e. fluidized fly ash and conventional one, and their mixtures on hydration of fly ash–cement compositions in relation to properties of final material. The amount of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Tables 1 and 2 summarizes the previous studies on wa of composites with the addition of siliceous FA with the provision of important parameters for these experiments, wchich were tested both in fully (table 1) and shallow immersion conditions (table 2). On the other hand, characterizes selected data on the implementation of wa experiments in concrete with the addition of other types of FA can be found, for example, in the works [120][121][122][123][124][125].…”
Section: Research Sigificancementioning
confidence: 99%
“…Tables 1 and 2 summarizes the previous studies on wa of composites with the addition of siliceous FA with the provision of important parameters for these experiments, wchich were tested both in fully (table 1) and shallow immersion conditions (table 2). On the other hand, characterizes selected data on the implementation of wa experiments in concrete with the addition of other types of FA can be found, for example, in the works [120][121][122][123][124][125].…”
Section: Research Sigificancementioning
confidence: 99%
“…Therefore, Table 1 summarizes the previous studies on composites with the addition of CFA with the provision of important parameters for these experiments. However, selected data on the implementation of water absorption experiments in concrete with the addition of other types of FA can be found, for example, in the works [82][83][84][85][86][87][88]. At this point, it should also be noted that a beneficial effect on the level of water absorption of the modified concretes, CFA and GGBFS, has been observed in the case of composites exposed to high temperatures [88,89,96,97].…”
mentioning
confidence: 99%
“…According to [64], the level of water absorption decreases in the case of cement binder substitution by CFA in a range of up to 35%. However, studies [83][84][85] prove that the addition of CFA from 30 to 90% causes a decrease in water absorption in these materials. However, the low water absorption in these studies was observed in concrete with 30% CFA.…”
mentioning
confidence: 99%